GC-MS Profiling and Antioxidant Activities of Ethanol Extract of Fresh Seeds of Miracle Tree-Moringa Oleifera lam - P, Arumugam; K, Saraswathi; C, Sivaraj (Asian Journal of Pharmaceutical Research and Development, 2020)
Objectives: Moringa oleifera Lam. or munga is one of the most important plant widely cultivated in India. It belongs to family Moringaceae. The plant is also known as Horse - radish tree, Drumstick tree. Every part of this plant contains a valuable medicinal feature. It contain rich source of the vitamin A, vitamin C and milk protein. Current research studies were carried out for evaluating the antioxidant activities and GC-MS analysis of ethanol extract of fresh seeds of Moringa oleifera. Methods: Antioxidant activities such as DPPH˙ radical, Superoxide (O2.-) radical, ABTS●+ radical cation, phosphomolybdenum reduction and Fe3+ reduction were carried out forthe ethanol extract of fresh seeds of Moringa oleifera. Identification of the active compounds present in the ethanol extract of fresh seeds of Moringa oleifera were detected by GC-MS profiling. Results: The maximum DPPH˙radical and Superoxide (O2.-) radical scavenging activities were79.28±0.43% and 63.8±0.26% at 120 µg/mL concentration and the IC50valueswere20.12 µg/mL and 85.91 µg/mL concentrations respectively. The maximum ABTS●+ radical cation scavenging activity was 83.26±0.37% at 12 µg/mL concentration and the IC50 value was 6.10 µg/mL concentration respectively. The maximum Mo6+ reduction and Fe3+ reduction were86.83±0.25% and 61.86±0.42% at 120 µg/mL concentration and the RC50 valueswere 18.20 µg/mL and 46.20 µg/mL concentrations respectively.Flavone, 7-Chloro-2,3-dihydro-3-methyl-5-phenyl-1H-benzodiazepin-2-one, Kaempferol, Pyrimidine,5-ethyl-2-[4-(4-ethylcyclohexyl)phenyl]-, 8-Carbethoxy-1-methyl-1,4,5,6,7,8-hexahydropyrrolo[2,3-b]azepin-4-one-3-carboxylic acid were the phytochemical compounds revealed from the ethanol extract of fresh seeds of Moringa oleifera by GC-MS profiling. Conclusion: The selected antioxidant methods and the GC-MS analysis proves Moringa oleifera as an potent antioxidant agent and thereby scavenge the free radicals existing in the environment.